Universally optimal circular neighbour balanced block designs under mixed effects model - Pateria, Dinesh Kumar; Jaggi, Seema; Varghese, Cini (Utilitas Mathematica, 2011)
This paper deals with optimality aspects of circular neighbour balanced block designs under mixed effects model, assuming block effects to be random. Combined intra-inter block educed normal equations for estimating direct and neighbour effects have been derived. Conditions have been obtained for the block design to be universally optimal for estimating direct and neighbour effects under mixed effects model. Some universally optimal familiesof circular neighbour balanced block designs have also been given.